The Role of National Income Estimates in the Statistical Policy of an Underdeveloped Area: A Comment - Prest, A. R. (Review of Economic Studies, 1953)
Journal Article The Role of National Income Estimates in the Statistical Policy of an Underdeveloped Area: A Comment Get access A. R. Prest A. R. Prest Cambridge Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 21, Issue 3, 1953, Pages 223–228, https://doi.org/10.2307/2295777 Published: 01 January 1953